Phytocomponents analysis and antioxidant activity of Malacca fruit extract (Phyllanthus emblica) using three different solvents - NAZARUDDIN NAZARUDDIN; ROSMAIDAR ROSMAIDAR; TONGKU N. SIREGAR; SRI WAHYUNI; AMALIA SUTRIANA (Society for Indonesian Biodiversity, 2024)
Abstract. Nazaruddin, Rosmaidar, Siregar TN, Wahyuni S, Sutriana A. 2024. Phytocomponents analysis and antioxidant activity of Malacca fruit extract (Phyllanthus emblica) using three different solvents. Biodiversitas 25: 1911-1919. Malacca plant (Phyllanthus emblica L.) grows widely in Aceh Province, Indonesia representing a wide group of phytochemical components of medicinal usage. This study aims to assess the antioxidant activity and bioactive compounds in P. emblica fruit extract, which was extracted by subsequent extraction using n-hexane, ethyl acetate, and ethanol. The extracts were then subjected to phytochemical and GC-MS to identify and quantify the bioactive compounds and measure the radical scavenging using DPPH assay to estimate the antioxidant activity. The results showed that P. emblica fruit extracted with ethanol and ethyl acetate contained flavonoids, phenolics, terpenoids, and saponin compounds, while n-hexane extract only contained steroids. The antioxidant activity of ethanol, ethyl acetate, and n-hexane extracts was very strong, with IC50 values of 18.81, 20.75, and 31.01 ppm, respectively. The highest antioxidant activity was found in the ethanol extract of P. emblica fruit. The GC-MS analysis revealed that the most abundant chemical component in ethanol and ethyl acetate extract was 1, 2, 3 benzenetriol, while in n-hexane extract was eugenol. Based on bioactive components and antioxidant activity, ethanol is suggested as the optimal solvent to gain a high content of polyphenols and flavonoids as well as high antioxidants from P. emblica fruit for utilization in pharmacognosy.